Distributed OPAC System Using Z39.50 Protocol - Y, Chandramohan Reddy; K, Madhuri (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Online Public Access Catalogue is playing a vital role in Central Libraries and University/College Libraries. Most of the College libraries are using OPAC for easy search and retrieval of the books and it's Status in a Particular Library. The main limitation in the OPAC we are using in current system is; that we are able to search and retrieve the information about the books of that particular library, but not outside of it. When we have a scenario like if we have multiple libraries in a campus, if we need to search a book in all the libraries, we have only two possibilities to build OPAC, once to make the single database for all the Libraries or you need to ask the user to search in all OPAC Systems of respective Library manually. But both above solutions are not feasible in real time environment. So in order to have the above scenario a feasible solution we need to build a distributed environment for the OPAC, which will have all the individual databases connected remotely.